Intercepción de lluvia en tres estadios sucesionales del Bosque seco Tropical, Parque Nacional Santa Rosa, Costa Rica - Jiménez-Rodríguez, César (Instituto Tecnológico de Costa Rica. Escuela de Forestal, 2010)
Rainfall, throughfall, stemflow and litter interception were measured in three sucesional stages of Tropical dry Forest in Santa Rosa National Park, Costa Rica. Three permanent plots of 1000m2 were used to estimate total Rainfall Interception (RI). The floristic composition and forest structure were described using the Holdridge Complexity Index [HCI], Vegetal Area Index [VAI-Licor-2000] and Canopy Cover [CC in %]. Al these indices increased with the maturity of each sucesional stage. The sample size was of 53 days, with a sampled total rainfall range of 327,22 mm, 272,06 mm and 471,29 mm for early, intermediate and late forest stage respectively. The RI in the early forest was around 20,99%, 40,99% in the intermediate and 55,87% in the late stage. The stemflow was less than 1% of the incident rainfall and the rain interception by the litter layer was around 2%. The RI increased linearly with the VAI. By the differences observed among sucesional stages of Tropical dry Forest it is recommended to evaluate independently each forest stages for futures studies.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2010.
Keywords: Flujo de fustes; Flujo de copas; Flujo de mantillo; Hidrología forestal; Bosque secundario; Rainfall interception; Stemflow; Throughfall; Litter-interception; Tropical